The COVID-19 Response of BRICS and Multilateral Development Banks - R. L. Silva; T. F. Almeida (BRICS Law Journal, 2023)
This article conducts an analysis of the BRICS member countries in terms of their national and international institutions, with a special emphasis on how these institutions affect the stability of the global financial system and the promotion of development. To this end, the work was guided by the attributions of national central banks and the role played by the G20 in maintaining international financial stabilization. Additionally, the analysis examines the activities of national development banks and their institutions established within the BRICS nations, such as the Contingent Reserve Arrangement and the New Development Bank. The descriptive method was used to interpret the dynamics of international political and legal relations. The article concludes by recognizing the decreasing significance of multilateral solutions and highlighting the need for the national central and development banks of the BRICS countries to engage in communication with international organizations of financial cooperation.